813. Implementing a Nurse-driven Nasal Decolonization Intervention to Prevent Surgical Site Infections within the Veterans Health Administration. (4th December 2021) - Sherlock, Stacey Hockett; Goedken, Cassie; Balkenende, Erin C; Dukes, Kimberly; Perencevich, Eli N; Reisinger, Heather Schacht; Schweizer, Marin L
Abstract: Background: Staphylococcus aureus surgical site infection (SSI) is common and devastating clinically. Pre-operative decolonization is associated with reduced incidence, but has been variably adopted due to barriers implementing high-efficacy prevention bundles, including unintentional non-compliance applying intra-nasal mupirocin by patients at home. Three Veterans Affairs (VA) facilities attempted to implement an alternate evidence-based SSI prevention program that included intranasal povidone-iodine used in the pre-operative setting to reduce challenging patient-burden steps and to overcome other mupirocin barriers. Our objective was to identify strategies used for successful implementation of intranasal povidone-iodine. Methods: We conducted pre- and post-implementation semi-structured interviews and site visits at three VA hospitals. Participants included surgery and clinic staff (e.g., nurses, physicians, care managers), infection control staff, and administrative leadership. Interviews were audio recorded and transcribed. Our interdisciplinary team performed a deductive and inductive consensus-based analysis. Results: Implementation of this SSI prevention process was successful when nurse champions drove the implementation. Qualitative interviews indicate that nurses used a variety of strategies and messages variant on their audience. Nurse-driven facilitators included: key leadership buy-in and strategic decisions about timing and setting of implementation (i.e., start implementation in units with likely early adopters then when project is working well circle back to the early detractors). The primary implementation barrier identified was lack of a champion. One site stated that in the absence of a champion, a mandate or top-down approach may be needed for implementation at their facility. Conclusion: Nurse champions facilitated successful SSI prevention process implementation. Nurses used strategies and approaches dependent on their knowledge and understanding of the stakeholders and setting to obtain buy-in. Future implementation of new clinical practices should consider utilizing nurse champions to promote uptake. Disclosures: Marin L. Schweizer, PhD, 3M (Grant/Research Support)PDI (Grant/Research Support)